2010
DOI: 10.1111/j.1740-8709.2010.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of lipid-based nutrient supplements (LNS) among Ghanaian infants and pregnant or lactating women

Abstract: Inadequate micronutrient intake during pregnancy, lactation and infancy is a major problem in many developing countries. Lipid-based nutrient supplements (LNS) can improve micronutrient status, growth and development of infants, and also have potential to improve nutritional status of pregnant and lactating women. The objective of the study was to test the acceptability of LNS designed for infants (LNS-20gM) and pregnant or lactating women (LNS-P&L). Participants were infants (n = 22, mean age = 8 months) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
100
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 11 publications
11
100
3
Order By: Relevance
“…LNSs have been widely used in the field of child malnutrition and are well accepted by children and caregivers (12,51,52). Current LNSs are typically made from vegetable oil, peanut paste, milk powder, sugar, and a micronutrient premix.…”
Section: Discussionmentioning
confidence: 99%
“…LNSs have been widely used in the field of child malnutrition and are well accepted by children and caregivers (12,51,52). Current LNSs are typically made from vegetable oil, peanut paste, milk powder, sugar, and a micronutrient premix.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of an adherence study conducted within a refugee emergency nutrition programme and it proposes thresholds for defining adequate acceptability and adherence for similar products in these contexts. Unlike other recently reported adherence studies (12,13,21) , the method is designed to allow the measurement of both under-and overconsumption during feeding at home and calculates adherence taking both of these behaviours in to account. When assessing the use of highly fortified products, such as those we tested, the ability to measure overconsumption is particularly important.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Bioavailability studies on MNP have shown that iron is well absorbed in infants (8,9) and multiple randomized studies have demonstrated the efficacy of MNP in treating anaemia in young children (10) . The acceptability of various LNS and MNP products was previously tested and generally found to be high in Pakistan (11) , Ghana (12) , Burkina Faso (13,14) and Malawi (15) . However, studies in refugee contexts have indicated that MNP is not always well accepted and that adherence can be low (16) .…”
mentioning
confidence: 99%
“…However, the weakness is that compliance/adherence to the study food was not checked, limiting our understanding of how the supplement was used by each child and within the household. The positive impact of LNS in these settings is likely to be associated with its good taste and acceptability among infants and young children (17)(18)(19) , its high energy and nutrient density, and its non-resemblance to normal family foods (5,20) . CSB, on the other hand, is normally consumed by infants as high-volume porridge, similar to many traditional foods.…”
Section: Discussionmentioning
confidence: 99%